PENINGKATAN HASIL BELAJAR IPA MATERI SUMBER- SUMBER ENERGI MELALUI METODE EKSPERIMEN - nurmardiah . (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2019)
Abstract This classroom action research aims to determine the improvement of student learning outcomes after the implementation of the Experimental method in class II SDN Seuneubok China in the first semester of 2017/2018 Academic Year, especially in science subjects, material, energy sources. This research was conducted with classroom action research methods conducted in 2 (two) cycles. Based on the results obtained during the implementation of class action research, it can be explained that student learning outcomes from the initial conditions of student learning outcomes are still low because under KKM ≥70, the class average is only 57.27 with classical learning completeness from 22 students only 8 students (36.36%) completed. In the first cycle after the experimental method was applied the average grade increased to 69.09 with classical completeness of 72.73% but the results have not reached KKM ≥70. In the second cycle, the class average increased again, reaching an average value of 80.45 with classical completeness of 95.46%. With the increase in learning outcomes in each cycle, the action hypothesis can be accepted and thus it can be concluded that the use of the exeriment method can improve the learning outcomes of science materials on energy sources in class II SD Seuneubok State of China